NEW CONCERNS REGARDING THE INNOVATIVE FORMULATION OF SOME PUDDINGS BASED ON GOAT MILK - Elisabeta Botez; Gabriel-Dănuț Mocanu; Doina Georgeta Andronoiu; Ana Cosmina Chirilă; Alina Balan; Daniela Constandache; Oana-Emilia Constantin; Oana-Viorela Nistor (Agricultura, 2018)
While consumers are more demanding about some ready-to-eat products, especially for sweets and desserts and they have high quality expectations, the producers are determined to be connected to their special necessities. So, puddings are very popular desserts, which are consumed all over the world in various formulations. The preparation of the samples was based on a classical idea which was innovated by replacing the important constituents of the formulation. Just due to its popularity the pudding reformulation is a challenge in accordance with the consumers’expectations which needs to recognize the specific characteristics of the puddings. First, the base of the pudding was the goat milk with some auxiliary materials as starch, agar, yolk powder, and Agave syrup, with/without coconut oil or Carob powder, vanilla/rum flavor.The four types of puddings (with vanilla, vanilla and coconut oil, Carob powder and Carob powder and coconut oil) were evaluated by physico chemical, microbiological, sensorial and energetic value.